(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
In an ontological sense, modernity is a way of existence of someone or something . Modernity in the praxeological sense is a branch of scientific research, which deals with the methods of all deliberate human activities . Modernity in the axiological sense is a science of values. If physical activity is subjected to in -depth research and analyzes, it is characterized by a clear dualism in an ontological sense, which is a consequence of needs. On the one hand, physical activity improves man’s physical condition and strengthens the body, and on the other, it causes growth and regeneration of neurons, which improves intellectual processes, i.e. human perception. Only a combination of physical activity and science can bring the expected educational effects at any level of education. In a pragmatic sense, the sports results of the individual or team are the clearly defined goal of physical activity. This often leads to the use of training methods or support with external products, i.e. chemicals, as well as medical and nutritional products, which use, among others Biological forms such as blood transfusions. The effects are as follows: from a axiological point of view, physical activity directs action excluding all other values except success. Success creates reality, it is generated by interdisciplinary issues with the possibility of violating human health in the name of the idea of winning above all. Such success can lead to dehumanization of sport and dehumanization of human beings. The concept of humanism and fair play is gradually lost. The above questions form the basis for investigation, which becomes a research challenge.